Regulation of Myostatin on the Growth and Development of Skeletal Muscle - Chen, Ming-Ming; Zhao, Yi-Ping; Zhao, Yue; Deng, Shou-Long; Yu, Kun (Frontiers in Cell and Developmental Biology, 2021)
Myostatin (MSTN), a member of the transforming growth factor-β superfamily, can negatively regulate the growth and development of skeletal muscle by autocrine or paracrine signaling. Mutation of the myostatin gene under artificial or natural conditions can lead to a significant increase in muscle quality and produce a double-muscle phenotype. Here, we review the similarities and differences between myostatin and other members of the transforming growth factor-β superfamily and the mechanisms of myostatin self-regulation. In addition, we focus extensively on the regulation of myostatin functions involved in myogenic differentiation, myofiber type conversion, and skeletal muscle protein synthesis and degradation. Also, we summarize the induction of reactive oxygen species generation and oxidative stress by myostatin in skeletal muscle. This review of recent insights into the function of myostatin will provide reference information for future studies of myostatin-regulated skeletal muscle formation and may have relevance to agricultural fields of study.